The Role and Impact of UNICEF Indonesia in Preventing and Addressing Out-Of-School Children: A Systematic Literature Review - Queentina Adhella Prudencia (Fakultas Ekonomi & Bisnis Universitas Paramadina, 2026)
The issue of out-of-school children (OOSC) remains a persistent challenge within Indonesia's education system, particularly in remote and marginalized regions where disparities in access, infrastructure, and socioeconomic conditions continue to hinder educational equity. As one of the Government of Indonesia's strategic partners, UNICEF plays a significant role in catalyzing the strengthening of policies, programs, and inclusive education interventions for children at risk of being left behind. This study aims to analyze the role and influence of UNICEF Indonesia in addressing the issue of out-of-school children through a Systematic Literature Review (SLR). The review was conducted by systematically collecting and examining scholarly publications and official reports from databases such as Google Scholar and the UNICEF Indonesia website, using keywords including “UNICEF Indonesia”, “quality education”, “out-of-school children”, and “strategic partnership”. A total of 16 articles and four reports met the inclusion criteria. They were analyzed thematically with respect to the scope of intervention, methodological approach, and key findings related to Indonesia’s government-UNICEF collaboration. The results reveal that the partnership between the Government of Indonesia and UNICEF has significantly improved access to and the quality of education through programs such as early-grade literacy initiatives in Papua, non-formal education pathways for marginalized groups, and the Child-Friendly Cities Initiative in urban areas. Furthermore, cross-sectoral collaboration among government, civil society organizations, and international partners has enhanced policy effectiveness in reducing the number of out-of-school children. This study emphasizes that evidence-based strategic partnerships and participatory approaches are key factors in promoting inclusive and sustainable education aligned with “Quality Education,” the fourth Sustainable Development Goal (SDG 4).